1992
DOI: 10.1164/ajrccm/145.6.1477
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocytes and Activated Eosinophils in Airway Mucosa in Fatal Asthma and Cystic Fibrosis

Abstract: With the use of monoclonal antibodies (mAb) and immunohistology, the numbers of phenotypically distinct cells infiltrating lung tissue from 15 postmortem (PM) cases of fatal asthma were quantified and compared with 6 cases of cystic fibrosis (CF) (three postmortem, three transplant) and 10 nonasthmatic cases of sudden death matched for age and sex. Tissue eosinophilia was significantly greater (p less than 0.001) in the fatal asthma group than in the CF or sudden death controls. In asthma, approximately 40% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
91
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 9 publications
6
91
1
1
Order By: Relevance
“…In cases of fatal asthma, the numbers of eosinophils were more closely related to the number of lymphocytes than in the nonfatal asthma and control cases. Numerous studies [3,12,15,16,19,20,24,[32][33][34] have shown increased numbers both of lymphocytes and eosinophils in asthmatic airways, although not over the range of asthma severity and airway sizes sampled in this study. It has been suggested that cell/ endothelial adhesion mechanisms and chemoattractant cytokines [35][36][37][38] may provide a common pathway of extravasation for lymphocytes and eosinophils at sites of inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…In cases of fatal asthma, the numbers of eosinophils were more closely related to the number of lymphocytes than in the nonfatal asthma and control cases. Numerous studies [3,12,15,16,19,20,24,[32][33][34] have shown increased numbers both of lymphocytes and eosinophils in asthmatic airways, although not over the range of asthma severity and airway sizes sampled in this study. It has been suggested that cell/ endothelial adhesion mechanisms and chemoattractant cytokines [35][36][37][38] may provide a common pathway of extravasation for lymphocytes and eosinophils at sites of inflammation.…”
Section: Discussionmentioning
confidence: 52%
“…Presence of CD80, major histocompatibility class II, and the Th2-associated receptor CD294 on the surface of CF airway neutrophils suggests that these cells are undergoing a significant switch toward cooperative functions with T cells, as described in other chronic inflammatory conditions (20,22). T cells migrate to the CF airway mucosa (38) and could play a nonnegligible role in neutrophil immunomodulation (2). Further studies are needed to determine whether de novo receptor expression by neutrophils plays a role in mitigating or accelerating CF airway inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…In acute allergic airway inflammation, eosinophils and macrophages constitute >80% of total recovered leukocytes 3,5,14 . Although allergic inflammation may be harmful to any organ, the host is particularly susceptible to lung involvement due to the potentially lethal effects of the inflammatory cells on gas exchange 39 . We showed that 100% mortality occurred in MMP2 −/− mice compared to 20% in wild-type mice (P<0.008).…”
Section: Discussionmentioning
confidence: 99%